Apoptosis in Human Papillomavirus-Induced Cervical Cancer Cells By Higher Doses of Ascorbic Acid - Zunaira Ali Baig; Amir Rashid; Ambreen Gul; Imran Raza; Asifa Majeed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the anti-cancer role of ascorbic acid using high doses against the cervical cancer cell line and to establish a cell culture facility in the laboratory.